INSTRUMENTS FOR RISING INTEGRATION PROCESS EFFICIENCY - M. V. Dzhioev (Real Economics Publishing House, 2015)
A motivating factor for performing amalgamation and merger is synergetic effect, creation of new opportunities for business development, increase in compatibility and financial viability of a new organization. However, up to 70% of all transactions are not efficient and lead to splitting of the united company. The article examines new instruments used in conducting such transactions. The principles of rising integration process efficiency are rationalized.